SAT0264 Valvulopathy and pulmonary hypertension in a series of patients with antiphospholipid syndrome. (15th June 2017) - Robles, A; Núñez, MJ; Rodríguez-Castellano, E; Busca, C; Ríos, JJ; Noblejas, A; Arnalich, F; Martínez, E
Abstract : Objectives: To evaluate the prevalence of cardiac valvular involvement and pulmonary arterial hypertension (PAH) and predictive risk factors in a cohort of patients with antiphospholipid antibodies. Methods: We included 232 patients from our cohort who underwent an echocardiogram. A total of 84 (36%) patients with primary antiphospholipid syndrome (PFS), 47 (20%) with APS secondary to systemic lupus erythematosus (SLE), 47 (20%) patients with antiphospholipid antibodies 23%) with SLE without AAF. The determinations of AAF and lupus anticoagulant were performed according to the indications of the international thrombosis society. Statistical analysis was performed with SPSS 18; using the Chi square test and the Fisher exact test. Results: In patients with AAF, the echocardiogram was pathological in 88 patients (52%) (p=0.023). Valvular affectation was evidenced in 64 (38%) (p=0.005) and PAH in 16 (p = ns). Seventeen patients (35%), SAF (48%), SAFS (26%), AIF silent (14%) and 9 patients in the non-AAF group (12%) presented with valvular affectation (p=0.002). PAH presented 19 patients, 9 with SAFP (47%), 6 in the SAFS group (32%), 1 in the silent AAF group (5%) and 3 in the non-AAF group (16%) (p= ). Both PAH and valvular involvement were asymptomatic in most cases, although two patients required valvular replacement. The most frequently affected valve in all groups was mitral valve (84%), except in patients with PAH where the most prevalent valvular pathology was tricuspid insufficiency. Patients with valvulopathy and APS had a higher prevalence of total thrombosis than SAF without valvulopathy (p=0.05). Patients with valvulopathy also significantly increased stroke and thrombocytopenia (p=0.04). Patients with valvulopathy had lupus anticoagulant more frequently (p=0.04), with no difference for the rest of AAF. Conclusions: Subclinical valvular involvement is very common in patients with AAF. Every patient with AAA should be given an echocardiogram in the initial protocol of their study in order to rule out both significant valvulopathy and PAH that can modify the management of the condition. Disclosure of Interest: None declared